2001
DOI: 10.1161/01.cir.103.6.799
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of ACE Inhibition and Angiotensin II Type 1 Receptor Antagonism on Bioavailability of Nitric Oxide in Patients With Coronary Artery Disease

Abstract: Thirty-five patients with CAD were randomized to 4 weeks of ACEI (ramipril 10 mg/d) or AT(1)-A (losartan 100 mg/d). FDD of the radial artery was determined by high-resolution ultrasound before and after intra-arterial N-monomethyl-L-arginine (L-NMMA) to inhibit NO synthase and before and after intra-arterial vitamin C to determine the portion of FDD inhibited by oxygen free radicals. EC-SOD activity was determined after release from endothelium by heparin bolus injection. FDD was improved after ramipril and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
216
2
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(239 citation statements)
references
References 36 publications
16
216
2
5
Order By: Relevance
“…8 Basic research has clearly demonstrated that the Ang II-mediated signal transduction pathway induces inflammation and oxidative stress. 9,10 In the clinical setting, ACEI and ARB reportedly improve endothelial function by increasing endothelium-bound (released by heparin injection) extracellular superoxide dismutase (EC-SOD) activity, 6 supporting the above observations. In addition, several pathological statuses have been reported to be associated with endothelial dysfunction, such as diabetes, 11 dyslipidemia 12 and chronic kidney diseases, 13 and RAS inhibitors improved endothelial dysfunction under these conditions.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…8 Basic research has clearly demonstrated that the Ang II-mediated signal transduction pathway induces inflammation and oxidative stress. 9,10 In the clinical setting, ACEI and ARB reportedly improve endothelial function by increasing endothelium-bound (released by heparin injection) extracellular superoxide dismutase (EC-SOD) activity, 6 supporting the above observations. In addition, several pathological statuses have been reported to be associated with endothelial dysfunction, such as diabetes, 11 dyslipidemia 12 and chronic kidney diseases, 13 and RAS inhibitors improved endothelial dysfunction under these conditions.…”
Section: Introductionmentioning
confidence: 68%
“…Both angiotensin converting enzyme inhibitors (ACEIs) and angiotensin II (Ang II) type 1 receptor antagonists (ARB) are essential drugs for such patients, 5 and have been reported to restore decreased endothelial function by improving NO availability. 6 However, it is still controversial whether improvement of endothelial function is an effect of the RAS inhibitor class because several investigators were unable to observe such an effect for ARB 7 in spite of beneficial effects seen for other classes of antihypertensives. 8 Basic research has clearly demonstrated that the Ang II-mediated signal transduction pathway induces inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…6 Restoration of Ec-SOD availability is associated with improvement of endothelial function in patients with CAD and is related to reduction of oxidative stress in vessel wall. 5 Earlier studies carried out in rats have shown that infusion of recombinant Ec-SOD protein resulted in reduced levels of creatine kinase in the left ventricular free wall and SOD bound to endothelial surface was also associated with lower cardiac damage in Langendorffperfused rat hearts subject to 15 min of global ischemia followed by reperfusion. 36 Subsequent comparative study conducted on infusion of recombinant Ec-SOD protein, Ec-SOD plus catalase and catalase alone showed inverse relationship between infarct size and creatine kinase levels in a pig myocardium injury model.…”
Section: Discussionmentioning
confidence: 99%
“…4 A number of recent clinical studies have reported reduced levels of human extracellular superoxide dismutase (Ec-SOD) in patients with coronary artery disease and myocardial infarction. [5][6][7] Superoxide anion is product of oxygen metabolism and is produced by activated inflammatory cells. [8][9][10] SODs are family of metalloproteins that scavenges superoxide anion radicals and form oxygen and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with essential hypertension, treatment with cizalapril for 2 years and lisinopril for 3 years improved vascular responses to acetylcholine in the subcutaneous microcirculation 4,[116][117][118] . Furthermore, within the peripheral circulation, perindopril, ramipril, quinapril and the perindopril-indapamide combination improve flowmediated dilatation, which most likely relates to increased NO bioavailability and prevention of angiotensin-II induced oxidative stress 4,35,37,115,[119][120][121] . ACE inhibitors may also potentiate bradykinin activity, which stimulates release of NO, PGI 2 and EDHF from the endothelium 22 .…”
Section: Ace Inhibitors and Angiotensin II Receptor Blockersmentioning
confidence: 99%